2019
DOI: 10.1371/journal.pone.0223101
|View full text |Cite
|
Sign up to set email alerts
|

Group conquers efficacy: Preschoolers’ imitation under conflict between minimal group membership and behavior efficacy

Abstract: Research has found that preschoolers’ imitation demonstrates in-group bias and is guided by behavior efficacy. However, little is known about whether children’s sensitivity to behavior efficacy affects their in-group imitation. This study aimed to investigate preschoolers’ imitation tendency when group preference and behavior efficacy are in conflict. Participants were 4-year-old (N = 72) and 6-year-old (N = 72) preschoolers in China. They observed two demonstrators (one in-group and one out-group) pressing tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…For example, many human developmental studies use the word 'imitation' when referring to tasks that may not be considered 'imitation' in the animal literature (e.g. Li, Liao, Cheng, & He, 2019). Thus, the impression that there is widespread presence of some mechanisms in humans but only limited presence in other animals might, at least in part, be explained by semantic differences, rather than differences in the way things actually are.…”
Section: The Abc Of Social Learningmentioning
confidence: 99%
“…For example, many human developmental studies use the word 'imitation' when referring to tasks that may not be considered 'imitation' in the animal literature (e.g. Li, Liao, Cheng, & He, 2019). Thus, the impression that there is widespread presence of some mechanisms in humans but only limited presence in other animals might, at least in part, be explained by semantic differences, rather than differences in the way things actually are.…”
Section: The Abc Of Social Learningmentioning
confidence: 99%
“…This effort is partially motivated by the desire to determine which aspects of imitation may be more culturally invariant and which are more variable and dependent on cultural context. A range of topics within social learning, using different paradigms, have been tested using non-Western samples (e.g., Nielsen and Tomaselli, 2010;Nielsen et al, 2014;Berl and Hewlett, 2015;DiYanni et al, 2015;Wang et al, 2015;Clegg and Legare, 2016;Corriveau et al, 2017;Taniguchi and Sanefuji, 2017;Hoehl et al, 2019;Li et al, 2019). However, little research has investigated the imitation of preschool children born and raised within China, a country that more than 1 billion people (for exceptions see Wang et al, 2015;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This effort is partially motivated by the desire to determine which aspects of imitation may be more culturally invariant and which are more variable and dependent on cultural context. A range of topics within social learning, using different paradigms, have been tested using non-Western samples (e.g., Itakura et al, 2008;Nielsen and Tomaselli, 2010;Nielsen et al, 2014;Berl and Hewlett, 2015;DiYanni et al, 2015;Wang et al, 2015;Clegg and Legare, 2016;Corriveau et al, 2017;Taniguchi and Sanefuji, 2017;Hoehl et al, 2019;Li et al, 2019). However, little research has investigated the imitation of preschool children born and raised within China, a country that more than 1 billion people (for exceptions see Wang et al, 2015;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One potential contribution is that we systematically crossed prior self-experience and pedagogical cues in a study of children in China. To date, only two experimental studies of imitation have been reported from China (Wang et al, 2015;Li et al, 2019). In Wang et al's (2015) study, the researchers examined whether children could categorize objects by weight after observing the adult's demonstration of such sorting behavior, and the results showed that 4-year-olds, but not 3-year-olds, imitated the categorization rule (sort visually identical objects by the hidden property of weight, which might have been interpreted by children as a social norm or convention).…”
Section: Rationale and Novelty Of The Studymentioning
confidence: 99%